INVESTASI PUBLIK DENGAN WAKAF TUNAI - Iin Emy Prastiwi; Fajar Fitrianingsih; Nasrudin Rama Sinudarsono; Zulkifli Rosyid Abdillah (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to discuss public investment through cash waqf. This study uses a qualitative method. Data collection techniques using literature study. The results in this study are cash waqf have an impact on the economy in general. Cash waqf as a social investment can be allocated to the construction of public facilities such as toll roads, hospitals and other developments. The allocation of cash waqf in the development is able to increase total investment in Indonesia so as to absorb unemployment. Waqf is not affected by the level of expected return (investment profit). Because waqf is voluntary where its movement is influenced by the level of community faith